2012
DOI: 10.1136/vr.100270
|View full text |Cite
|
Sign up to set email alerts
|

Detection of elephant endotheliotropic herpesvirus type 1 in asymptomatic elephants using TaqMan real‐time PCR

Abstract: This study assessed the feasibility of identifying asymptomatic viral shedders using a novel TaqMan real-time PCR on trunk washes and swabs from the conjunctiva, palate and vulva of elephants. Six elephants from a UK collection were sampled weekly over a period of 11 weeks for this study. The herd prevalence of elephant endotheliotropic herpesvirus-1 (EEHV-1) was 100 per cent by PCR. The virus DNA was detected in all the sampling sites; however, the prevalence of virus DNA in the conjunctiva swabs was higher. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 14 publications
3
47
0
Order By: Relevance
“…This study suggested that EEHV1 was most likely to belong to a group of endogenous viruses that co-evolved with Asian elephants, rather than being transmitted from African elephants (Zachariah et al, 2013). This theory was also supported by the fact that EEHV1 was found to be shed occasionally from adult Asian elephants which showed no clinical signs (Hardman et al, 2012;Stanton et al, 2013), thus adult elephants could potentially play a role as a viral reservoir.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…This study suggested that EEHV1 was most likely to belong to a group of endogenous viruses that co-evolved with Asian elephants, rather than being transmitted from African elephants (Zachariah et al, 2013). This theory was also supported by the fact that EEHV1 was found to be shed occasionally from adult Asian elephants which showed no clinical signs (Hardman et al, 2012;Stanton et al, 2013), thus adult elephants could potentially play a role as a viral reservoir.…”
Section: Introductionmentioning
confidence: 66%
“…This is suggested that a single locus analysis may not be sufficient to draw a conclusion concerning epidemiological relatedness and multiple gene analysis is needed. EEHV is shed in elephant secretions including those from trunk and conjunctiva (Hardman et al, 2012;Atkins et al, 2013;Stanton et al, 2013), with evidence this shedding pattern is intermittent (Hardman et al, 2012), thus it is likely there is ongoing exposure within a herd. The findings from our study also suggested that disease occurrence is sporadic despite the high likelihood of all animals encountering the virus, and therefore the development of disease following EEHV infection likely depends on the host immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The virus targets preferentially elephants between the ages of 4 months and 15 years and causes considerable loss of captive elephants in zoological gardens in Asia (Reid et al, 2006). Recently, EEHV1 has been detected in healthy Asian elephants (Hardman et al, 2011;Schaftenaar et al, 2010;Stanton et al, 2010). Until now, EEHV could not be cultured from infected elephants with endothelial disease (Latimer et al, 2011;Ossent et al, 1990;Richman et al, 1999).…”
Section: Introductionmentioning
confidence: 95%
“…Hence, virus detection in exposed elephants was attempted mostly by viral genome detection by polymerase chain reaction (PCR) based methods and serological assay for antibody detection. There have been several reports on PCR developed to detect viral DNA in whole blood samples, post-mortem necropsied tissues, and trunk washes (Fickel et al, 2001(Fickel et al, , 2003Garner et al, 2009;Hardman et al, 2011;Latimer et al, 2011;Stanton et al, 2010). However, a new test that has exceeded the sensitivity of these methods is available currently.…”
Section: Introductionmentioning
confidence: 95%
“…Although transfer events of this kind may have occurred, subsequent investigations have indicated that the epidemiology of EEHV infections is more complex (3,16,17). For example, EEHVs may circulate asymptomatically in Asian elephant populations; thus, they do not necessarily rely on interspecies transfer for disease development (18)(19)(20).…”
mentioning
confidence: 99%